Long-term optical polarization variability and multiwavelength analysis of Blazar Mrk 421 - Fraija, Nissim; Hiriart, David (Arxiv, 2017)
The results of 8-year R-band photopolarimetric data of blazar Mrk 421 collected from February 2008 to May 2016 are presented, along with extensive multiwavelength observations covering from radio to TeV $γ$-rays around the flares observed in May 2008, March 2010, and April 2013. The most important results are found in 2013 when the source displayed in the R-band a very high brightness state of $11.29± 0.03$ mag ($93.60± 1.53$ mJy) on April 10th and a polarization degree of ($11.00±0.44$) on May 13th. The analysis of the optical data shows that the polarization variability is due to the superposition of two polarized components that might be produced in two distinct emitting regions. An intranight photopolarimetric variability study carried out over 7 nights after the 2013 April maximum found flux and polarization variations on the nights of April 14, 15, 16 and 19. In addition, the flux shows a minimum variability timescale of $Δ\,t=$2.34$±$0.12 hours, and that the polarization degree presented variations of $\sim$ (1 - 2) in a timescale of $Δ\,t\sim$ minutes. Also, a detailed analysis of the intranight data shows a coherence length of the large-scale magnetic field of $l_B\simeq$ 0.3 pc which is the same order of magnitude to the distance traveled by the relativistic shocks. This result suggests that there is a connection between the intranight polarimetric variations and spatial changes of the magnetic field. Analysis of the complete R-band data along with the historical optical light curve found for this object shows that Mrk 421 varies with a period of 16.26 $±$ 1.78 years.
Gesehen am 10.10.2017